Analysis of the Impact of the Implementation of Priority Service Policy on Customer Satisfaction - Kusuma Wardhani, Anna; Widjanarko Otok, Bambang (LifeSciFi, 2025)
The change in the reliability service policy from Premium Service to Priority Service raises concerns about the potential decline in customer interest in this service. Priority Service is expected to be an alternative for customers with power capacities above 200 KVA, who require higher power supply reliability and service beyond regular standards. This study uses the Mixed Methods Research approach, where data collection is carried out both quantitatively and qualitatively. Quantitative data was obtained through a Likert scale questionnaire and analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS) to assess customer satisfaction based on the SERVQUAL approach, which included the variables Reliability, Assurance, Tangibility, Empathy, and Responsiveness, combined with additional variables such as Service Price, Service Delivery, and Expected Service. Meanwhile, qualitative data was collected through interviews to support the findings obtained from the quantitative analysis. The findings of the study show that Assurance, Empathy, and Reliability have a significant influence on Service Quality, while Tangibility and Responsiveness have no significant impact. In addition, Service Delivery, Expected Service, and Service Quality have the most dominant influence on Customer Satisfaction, while Service Price also affects satisfaction but with a lower level of significance. However, the results of the study may vary depending on the characteristics of each unit's customers. Most customers come from the industrial sector.